Individual-specific changes in the human gut microbiota after challenge with enterotoxigenic Escherichia coli and subsequent ciprofloxacin treatment. (December 2016) - Pop, Mihai; Paulson, Joseph; Chakraborty, Subhra; Astrovskaya, Irina; Lindsay, Brianna; Li, Shan; Bravo, Héctor; Harro, Clayton; Parkhill, Julian; Walker, Alan; Walker, Richard; Sack, David; et al.
Abstract Background EnterotoxigenicEscherichia coli (ETEC) is a major cause of diarrhea in inhabitants from low-income countries and in visitors to these countries. The impact of the human intestinal microbiota on the initiation and progression of ETEC diarrhea is not yet well understood. Results We used 16S rRNA (ribosomal RNA) gene sequencing to study changes in the fecal microbiota of 12 volunteers during a human challenge study with ETEC (H10407) and subsequent treatment with ciprofloxacin. Five subjects developed severe diarrhea and seven experienced few or no symptoms. Diarrheal symptoms were associated with high concentrations of fecalE. coli as measured by quantitative culture, quantitative PCR, and normalized number of 16S rRNA gene sequences. Large changes in other members of the microbiota varied greatly from individual to individual, whether or not diarrhea occurred. Nonetheless the variation within an individual was small compared to variation between individuals. Ciprofloxacin treatment reorganized microbiota populations; however, the original structure was largely restored at one and three month follow-up visits. Conclusion Symptomatic ETEC infections, but not asymptomatic infections, were associated with high fecal concentrations ofE. coli . Both infection and ciprofloxacin treatment caused variable changes in other bacteria that generally reverted to baseline levels after three months.